Erosion surface and granitic morphology in the Sierra de Lihuel Calel, Province of La Pampa, Argentina - Aguilera, Emilia Yolanda (2014)
This chapter aims to characterize the landforms of the ignimbrite landscape in the Sierra de Lihuel Calel, province of La Pampa, Argentina. DEM data from SRTM were used for the analysis of morphometric characteristics and other parameters, so as to obtain longitudinal profiles and identify the boundaries of the paleosurface. By means of the interpretation of satellite imagery and field observations, the different features of this ancient landscape were identified as well as the lithology and fabric of the volcanic and pyroclastic rocks, which were petrographically studied. Textural transformations occurring in ignimbrites provided properties to these rocks which are similar to those common in granitic rocks. The studied landforms might be regarded as pseudo-granitic landforms, and thus major and minor landforms are described. Fracturing has been found as a significant factor in landform evolution.